Nabrekanje glinenih zemljin - Daneu, Nina (Kovine zlitine tehnologije, 1998)
Compacted clay liners are often used as barriers in landfill sealing systems and objects that require special ground protection. Functions of mineral sealing layers as geotechnical barriers are: minimisation of permeability, adsorption of pollutants, resistance to erosion, self healing ability, resistance to swelling and shrinkage. Resistance of compacted clay liners to swelling and shrinkage is important because it can cause macrostructural defects such as cracks and discontinuities. It is related to hydrogeological conditions (water content), grain size distribution and mineral composition of clay. In this work we determined expansion degree of nine different clays from Slovenia. Out of nine different samples there were found useful for construction of compacted clay liners.
Keywords: petrografija; glina; nabrekanje; odlagališča odpadkov